2012
DOI: 10.1055/s-0032-1304301
|View full text |Cite
|
Sign up to set email alerts
|

MR and CT Arthrography of the Knee

Abstract: MR and CT arthrography are important imaging modalities for the assessment of the knee in certain situations. Indications for MR arthrography of the knee include assessment of the postoperative meniscus, the presence of chondral and osteochondral lesions, and the presence of intra-articular bodies. The major indication for CT arthrography is evaluating suspected internal derangement in patients who are unable to undergo MRI. In addition to reviewing the established clinical indications for MR and CT arthrograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 62 publications
0
36
0
Order By: Relevance
“…As such, component rotation could not be analyzed. It is likely that the MRI-based technique provides improved imaging of the cartilage surfaces [6,9,22,44,47]. Based on the cartilage surface estimated by the surgeon with CT-based patient-specific instrumentation, deviations from the real joint surface are possible, which can result in a poorer fit.…”
Section: Discussionmentioning
confidence: 99%
“…As such, component rotation could not be analyzed. It is likely that the MRI-based technique provides improved imaging of the cartilage surfaces [6,9,22,44,47]. Based on the cartilage surface estimated by the surgeon with CT-based patient-specific instrumentation, deviations from the real joint surface are possible, which can result in a poorer fit.…”
Section: Discussionmentioning
confidence: 99%
“…Besides MRI, CTA has been used for detection of osteochondral lesions in many joints [12, 17, 18, 2830]. CTA of the ankle joint is still clinically relevant [16] and the diagnostic value may be underrepresented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Chemouni et al CT arthrography showed an accuracy of 88% [31]. For detection of retropatellar osteochondral lesions, CTA performed superior compared with conventional MRI in several studies [1, 28]. For detection of osteochondral lesions at the ankle, Schmid et al reported that CTA was superior to MRA [6].…”
Section: Discussionmentioning
confidence: 99%
“…Arthrography can also be used to assess the status after autologous chondrocyte implantation and sometimes for assessment of anterior cruciate ligament grafts. 28 …”
Section: Articular Intervention Arthrography Indicationsmentioning
confidence: 99%
“…The most commonly used approach is the lateral patella-femoral approach but a medial patella-femoral or direct anterior approach (medial or lateral to the patellar tendon) may also be used. 28,31,32 The patient is positioned supine with the knee slightly flexed to enable the quadriceps to be relaxed. After obtaining informed consent, a sterile technique is used to infiltrate the skin and subcutaneous tissues with a small amount of appropriate local anaesthetic solution.…”
Section: Risks and Contraindicationsmentioning
confidence: 99%